Ecophilosophical meaning of Hildegard of Bingen’s thought - Łepko, Zbigniew; Sadowski, Ryszard F. (Studia Ecologiae et Bioethicae, 2014)
This article presents the medieval thought of Hildegard of Bingen, which seems to be very topical at this time of ecological crisis. In a prophetic way, this outstanding, European, medieval figure saw the challenges that civilized humankind faces in our time. In her works we find the roots of such popular ideas as a holistic view of the world and sustainable development. According to Hildegard of Bingen, original harmony between God, mankind, and the world is upset by irresponsible human deeds. Hildegard points out that mankind, which is the first victim of its own deeds, is able to recognize a critical situation and take steps to overcome the crisis. Hildegard of Bingen’s work expresses optimism about mankind’s ability to change its attitude towards nature This optimism is derived from the spiritual and intellectual skills of mankind.